"Out, Damned Spot!" The Staining of the Proclamation of the Constitution Act, 1982 - Whalen, James Murray (Archivaria, 2006)
This article is an account of what happened when a vandal irreparably damaged an original copy of the Proclamation of the Constitution Act, 1982 at the (then) Public Archives of Canada while it was being shown to him. The writer of this piece, who was the victim of this malicious act, traces events in chronological order and shows how the document was created, its purpose, how it was stained, steps taken to restore it, and its value. As a result of the disaster, the Public Archives reevaluated procedures for handling prestigious documents in order to better protect them from harm. It also had to deal with an important ethical question – to what extent should conservators go to restore a document without affecting its authenticity and integrity? RÉSUMÉ Cet article est un compte-rendu de ce qui s’est passé quand un vandale a irrémédiablement endommagé une copie originale de la Proclamation de la Loi constitutionnelle de 1982 lorsqu’on la lui montrait aux Archives publiques du Canada. L’auteur de ce texte, qui fut la victime de cet acte malicieux, retrace les événements en ordre chronologique, puis il montre comment le document a été créé et dans quel but, comment il a été taché, quelles étapes ont été entreprises pour le restaurer et sa valeur. Suite à ce désastre, les Archives publiques ont réévalué leurs procédures pour manipuler des documents prestigieux dans le but de mieux les protéger du danger. Elles ont aussi eu à affronter une importante question éthique : jusqu’à quel point les techniciens de la conservation devraient-ils restaurer un document sans heurter son authenticité et son intégrité?